PS-011 Improving the system for monitoring adverse drug reactions. (24th March 2015) - Kim, M; Ahn, M; Song, S; Jung, Y; Jeong, H
Abstract : Background: This study examined adverse drug reaction (ADR) reports submitted at this hospital for 32 months from December 2011 to July 2014. The proportion of ADR cases reported by doctors and nurses was 8.7%, while that of pharmacists was 91.3%. Nevertheless, the proportions of ADR of injectables and other drugs reported by doctors and nurses were 4.0% and 6.1%, respectively. Thus, their ADR reporting should largely be improved. Purpose: To investigate the perception of ADR reporting by clinical staff, to examine what is done in response, and to seek to improve the monitoring system and invigorate ADR reporting. Material and methods: A survey was distributed to each department and ward. The completed questionnaires were collected from these participants three days later. Results: Of the participants, 36.5% knew about the ADR reporting procedure in the electronic medical record system. However, only 5.3% had actually reported ADRs. Of participating doctors, 66.7% did not report an adverse reaction since they felt it was too complex and were busy. Of participating nurses, 50.0% did not report ADRs since they were not sure of the cause-effect relationship. However, 28.6% of nurses did not report adverse reactions since they were too minor. To prevent ADR recurrence, 75.4% of clinical staff inputted ADR data into the medical record, while only 12.1% of them inserted such data into the ADR system. Conclusion: For periodic and vigorous promotion of ADR reporting, these authors began an all-out promotion which included distributing an official letter and making an ADR presentation at medical conferences. We are improving the system to simplify the reporting process and to effectively manage the reported cases. Additionally, the ADR feedback system is newly reinforced. We hope that such a feedback system may invigorate quality ADR reporting. References and/or acknowledgements: No conflict of interest.